How to Communicate CSR Activities? Should Companies Communicate Their Social Commitment? - Honorata HOWANIEC; Przemysław KASIŃSKI (Communications of International Proceedings, 2021)
CSR has become a reality in most enterprises, but there are still no clear indications, e.g. in the area of communicating the involvement of enterprises in socially desirable initiatives. Literature provides contradictory indications in this area. On the one hand, excessive CSR communication is negated, on the other hand it gives hints as to what form is desired by the society. Many companies, not wanting to be accused of deliberately undertaking CSR activities, e.g. for image-related purposes, do not communicate it at all. However, this is also not good. Lack of any information means that even the closest environment does not notice the company's activities in this area. The article tries to answer two questions whether enterprises should communicate CSR and whether the local community perceives the activities undertaken by companies for their benefit. The article uses the results of the interview and survey research. It was examined how CSR activities are perceived by a company that is very active in this area, but does not communicate it. The obtained results confirmed that the lack of any promotion of activities undertaken by the company means that they are not known in the immediate vicinity of the company. Therefore, it is recommended to communicate CSR activities at least to a minimum extent.
Keywords: CSR; corporate communication; CSR communication; stakeholders communication.